2012
DOI: 10.1016/j.jvs.2011.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic vein mapping prior to infrainguinal autogenous bypass grafting reduces postoperative infections and readmissions

Abstract: Routine DVM should be recommended for infrainguinal bypass surgery. The study found that preoperative DVM significantly avoids unnecessary surgical exploration, development of major SSI, and reduces frequency of readmissions for SSI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…There is an extensive variation in the reported incidence of SWI after lower limb vascular surgery. In prospective studies with the number of patients ranging from 69 to 561, the incidence of SWI was found to be between 3.5% and 32% (313).…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…There is an extensive variation in the reported incidence of SWI after lower limb vascular surgery. In prospective studies with the number of patients ranging from 69 to 561, the incidence of SWI was found to be between 3.5% and 32% (313).…”
Section: Incidencementioning
confidence: 99%
“…Another meta-analysis of 43 studies with 27,789 patients revealed that endoscopic vein harvesting reduces the risk of SWI in patients undergoing CABG compared with open technique (OR = 0.27; 95% CI = 0.22–0.32) (61). Furthermore, ultrasound vein mapping of the great saphenous vein reduced the risk of major SWI (1.9% vs 21.2%, p = 0.004) compared with no vein mapping in infrainguinal bypass surgery in a prospective randomized study of 103 patients (10). Using ultrasound vein mapping of great saphenous vein and minimally invasive vein harvest technique for lower limb revascularisation surgery may be beneficial in order to avoid SWI.…”
Section: Preventionmentioning
confidence: 99%
“…The majority of vascular surgery procedures are classified as clean surgery by the US National Research Council because they are performed in uninfected tissue without signs of inflammation [ 1 ]. The reported incidence of surgical wound infections after lower limb vascular surgery varies between 3.5 and 32 % [ 1 4 ]. Therapy for symptomatic chronic venous obstruction and post-thrombotic syndrome (PTS) has changed during the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has reported previously that thorough preoperative assessment of vein status in every patient is crucial for success of the operation. 2,3 We check the diameter of the vein and, if there is suspicion of varicose veins, we do check for valve dysfunction in the same assessment. We did not observe expansion of the vein graft either before or after the operation in any of these patients.…”
mentioning
confidence: 99%